AN ANALYSIS THE INFLUENCE OF SUBPROCESS IN PATIENT DISCHARGE TO A TIMELY MANNER DISCHARGE PROCESS IN XYZ HOSPITAL - Lilipaly, Angela Geraldine (Emerging Markets : Business and Management Studies Journal, 2018)
Health care services everywhere have many process in their system. Discharge process is a last process during the patient stay in the hospital. In this process there are many division involve which would impact the time needed for each patient discharge to be completed. And this would also impact the waiting time of admiting other patient. Waiting time issues for accessing and providing healthcare services is also an issue in many hospital and is also identify by the leaders of one of the hospital in South Tangerang area (XYZ Hospital). At the time a patient is plan to be discharge, they expect a timely and quality discharge from their care provider. Hospital might have limitation on human resources, or be lack of standardization, preparation, communication, which create a bottleneck in the system. There are several process that patient have to go through when doctor concluded that the patient could be discharge: Nursing Discharge (X1): the time from patient has been prepare for discharge by physician to the time of nursing dicharge. Pharmacy Discharge (X)2: the time from excepting discharge prescribtion untill pharmacy discharge. Financial Discharge (X3): the process of patient administration and payment. Discharge Education (X4) : time of education prior discharge given by the nurse and clinical pharmacist. While the Dependent variable is Time for patient discharge process (Y). The primary objective of this research is to explore and analyze those processes, where the hospital could identify which process is significant to improve, so the management of the hospital would focus the effort and support on those process/s; which then would make patient discharge moresufficient and will then also resulting the improvement of patient admission waiting time.The Statistic Model use for this research is Multiple Regression to examine the linear relationship between 1 dependent (Y) and 4 independent variable (X1, X2, X3, X4 ). Sample of inpatient patients which are discharge from the hospital. The sample of this research is by collecting secundary data; from December data which would be 248 patient discharge a month. By having this kind of measurement and analysis, it is expected that the hospital could identify which process is significant to improve, and the managment of the hospital would focus the effort and support on those process/s; which then would make patient discharge more sufficient and will then also resulting the improvement of patient admission waiting time. This research resulted that 3 out of 4 subprocesses influence patient discharge. The 3 subprocesses which impact significantly to patient discharge are: nursing, financial and education discharge processes.